Controversies in Healthcare Innovation Service, Technology and Organization (Palgrave Macmillan UK, 2018)
This book examines healthcare innovation processes, shedding light on the controversies endemic to innovation, which make such processes notoriously challenging. While, in the heat of action, controversies may be seen as barriers to innovation, observations reported in this volume point to controversies also having an energizing role. Students and academics studying innovation, organization, and health management and economics will find this book a valuable read as it provides empirical case studies on innovation processes in practice. Controversies in Healthcare Innovation will also appeal to practitioners of health care management, innovation project managers and policy-makers in the health care sector.